The International, 1864-1924 : [Programme commemoration demonstration in Lyceum Theatre, London, 28th September 1924 ; Celebration of the sixtiest anniverary of the foundation of the First International Working Men's Association] (London: Pelican Press, 1924)
"Bibliotheek Camille Huysmans"